Geopolitical Dynamics of Maritime Security in the Strait of Hormuz - Hasna Moraina Rizkiyani; Trismadi Trismadi; Asep Adang Supriyadi; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The Strait of Hormuz, a critical maritime passageway connecting the Persian Gulf to the Arabian Sea and Indian Ocean, plays a pivotal role in global energy trade. This study examines the multifaceted challenges surrounding this strategic waterway, which varies from 55 to 95 kilometers in width. The research explores the strait's economic significance, not only for Persian Gulf nations but for the global market, as evidenced by the high density of maritime traffic. The analysis encompasses the recurring security disturbances in recent decades, including tanker attacks and piracy incidents, which compound regional security complexities. Furthermore, the geopolitical dynamics of the Strait of Hormuz are scrutinized, particularly in relation to tensions between Iran, the United States, and Gulf states. Historical conflicts, such as the Iran-Iraq War and the First Gulf conflict, are evaluated to demonstrate the strait's impact on global oil prices and economic stability. The study also addresses challenges like theft and extortion, which further complicate navigation and maritime security. By providing a comprehensive analysis of the geographical, economic, and security characteristics of the Strait of Hormuz, this research aims to elucidate the challenges in maintaining regional and international stability, emphasizing the waterway's critical role in global energy security and international trade.